The Importance of Understanding Ability, Skills and Attitudes of Students in the Practice of Guidance and Counseling Services - Sutirna Sutirna; Safuri Musa (Kuras Institute, 2023)
The objective study is to know students' level of ability, understanding, skills, and attitudes in practice service guidance and counseling in schools. The approach research used is a study survey of guidance and counseling teachers who become tutors in accompaniment student practice guidance and counseling. Instruments in questionnaires closed as many as 25 items with indicator understanding, skills and attitudes students in implementation activity practice guidance and counseling. While processing techniques results survey uses percentages from many answer respondents compared amount whole respondents multiplied by 100%, the results percentage categorized as very good, good, well enough, less well, and very less. Research results conclude that students' level of ability in understanding, skills, and attitudes in implementation service guidance and counseling. The research results are concluded (1) the level of ability to understand guidance and counseling for students who carry out practices in schools is included in the sufficient category (very good 29.17% and good 56.25% ), (2) the level of students' skills in providing guidance and counseling services to students in the aspects of attending, responding, personalizing, and initiating is included in the sufficient category (very good 33.16% and good 56.88%), and (3) the level of ability of students' attitudes in carrying out guidance and counseling services in schools is categorized as sufficient (for very good 51.49% and good 41.96%).